Problems and prospects of development of the Shanghai cooperation organization - Baktymbet, A.S.; Gamarnik, G.N.; Baktymbet, A.S.; Baktymbet, S.S. (BUKETOV BUSINESS REVIEW, 2019)
The article deals with the main problems of mutual trade of the SCO countries, which are of particular relevance in the development of integration processes. The development of cooperation in mutual trade of the SCO member States sets the task of finding optimal mechanisms to increase the share of national currencies in mutual settlements between the SCO member States. Cooperation within the SCO is today one of the important directions of the foreign policy of the Republic of Kazakhstan. Constructive participation and focus on an equal dialogue with the SCO partner countries contributes to the growth of mutual trust and understanding between States, strengthens the position of Kazakhstan not only in the region but also at the international level as a guarantor of regional security and strategic stability on the Eurasian continent. The problems of development of cooperation caused by factors of internal and external environment are considered. The impact of the national economies of the participating countries, trends in the world economy and geopolitics. Proposals for the formation of a single SCO space are given.